2004
DOI: 10.1016/s0378-1097(04)00066-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of emetic toxin producingBacillus cereusstrains by a novel molecular assay

Abstract: Bacillus cereus causes two types of gastrointestinal diseases: emesis and diarrhea. The emetic type of the disease is attributed to the heat-stable depsipeptide cereulide and symptoms resemble Staphylococcus aureus intoxication, but there is no rapid method available to detect B. cereus strains causing this type of disease. In this study, a polymerase chain reaction (PCR) fragment of unknown function was identified, which was shown to be specific for emetic toxin producing strains of B. cereus. The sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 29 publications
2
94
0
Order By: Relevance
“…Cereulide is a small heat stable cyclic dodecadepsipeptide produced by some strains of B. cereus which has high toxicity to humans (1,36). Cereulide is synthesized by a non-ribosomal peptide synthetase, encoded by the ces genes located on a 270-kb pXOI-like virulence plasmid named pCER270 (10,26), more often found associated with clinical isolates of B. cereus. A recent study has reported the presence of cesA, but not cesB, in B. pumilus and B. licheniformis isolated from bovine mastitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Cereulide is a small heat stable cyclic dodecadepsipeptide produced by some strains of B. cereus which has high toxicity to humans (1,36). Cereulide is synthesized by a non-ribosomal peptide synthetase, encoded by the ces genes located on a 270-kb pXOI-like virulence plasmid named pCER270 (10,26), more often found associated with clinical isolates of B. cereus. A recent study has reported the presence of cesA, but not cesB, in B. pumilus and B. licheniformis isolated from bovine mastitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…DNA fragments of emetic and emetic-like strains were subcloned in Topo TA vector (Invitrogen) and sequenced as described previously (Ehling-Schulz et al, 2004b). The resulting sequences were searched against the sequenced genomes of B. cereus group strains and against the NCBI non-redundant protein database using BLAST (Altschul et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…systems have been developed for the identification of emetic strains and the detection of the toxin gene Ehling-Schultz et al, 2004Altayar and Surtherland, 2006 . However, the conventional PCR requires post-PCR analysis by gel electrophoresis and visualization steps, which take valuable time and may bear the risk of giving false-positive results due to laboratory contamination.…”
mentioning
confidence: 99%